EFFECT OF ELASTOMERIC SEPARATOR ON MICROBIAL COUNT IN GINGIVAL CREVICULAR FLUID - Sattar Khan, Samia; Asad, Saad; Hussain, Umar (Journal of Ayub Medical College Abbottabad, 2023)
Background: The separators are a preliminary step for band insertion, but there is a potential risk of bacteraemia during their placement, particularly in susceptible patients. The objective of the study is to determine the effect of separators on the bacterial count in gingival crevicular fluid (GCF) and to assess the efficacy of chlorhexidine mouth rinse and saline irrigation in the reduction of the bacterial count. Methods: This randomized controlled trial was conducted on 51 participants who were divided into three equal groups randomly (brushing only/control, saline irrigation, and 2% chlorhexidine mouthwash rinse). The inclusion criteria were age between 18-25 years, good oral hygiene, gingival and plaque index <1, no previous orthodontic treatment, and healthy individuals. The bacterial count was obtained from GCF samples after two hours, on the third day, and on the seventh day. Kruskal Wallis test was used to compare the bacterial count among the three groups, and post hoc analysis was done using Dunn’s test. Friedman test was applied to see the difference at three-time points in each group. Results: In both saline and chlorhexidine groups the mean bacterial count decreased significantly from baseline to 3rd day and 7th day after separator placement (p<0.001). For the third day, a significant difference was found in control versus saline and control versus chlorhexidine. No significant difference was found between saline and chlorhexidine on the third day. Similar results were found on the 7th day. For controls, the bacterial count increased with time and for both saline and chlorhexidine groups the bacterial count decreased. The highest decrease in the bacterial count was found for the chlorhexidine group. Conclusion: After the placement of separators, there was an increase in the bacterial count in GCF. Notably, chlorhexidine was found to be more effective than saline irrigation in reducing the bacterial count.